Study in sociology of literature - Ćorluka, Bojan J (Sociološki pregled, 2017)
Zoran Avramović Literati and politics in Serbian culture 1804-2014 - Beautiful Soul and Janus’ face of politics.Novi Sad, Pravoslavna reč, 2016, 288 pp